A new species of genus Campodorus (Hymenoptera, Ichneumonidae) from China - Wei, Ya-Wei; Sheng, Yuan-Jü (Zootaxa, 2024)
A new species of the genus Campodorus Förster, 1869, C. concavus Wei & Sheng, sp. nov., collected from the Research Station of Liaohe-River Plain Forest Ecosystem, Zhangwu, Liaoning Province, and the forest of Pinggu District, Beijing, China, is described and illustrated. A key to the similar species of Campodorus is provided.